Complexity of Culture and Challenges to Learning: A Case Study of Eastern European Perspectives on Learning - Oleksandra Sehin (Adult Education Research Conference, 2014)
This qualitative pilot study will add to the adult learning and development literature by unfolding the complexities of Eastern European culture and migration, challenges to learning, and the importance of narrative to immigrant adult learning and development.